AN ANALYSIS ON USAGE PREFERENCES OF LEARNING OBJECTS AND LEARNING OBJECT REPOSITORIES AMONG PRE-SERVICE TEACHERS - Yeni, Sabiha; Ozdener, Nesrin (ANADOLU UNIV, 2014)
The purpose of the study is to investigate how pre-service teachers benefit from learning objects repositories while preparing course content. Qualitative and quantitative data collection methods were used in a mixed methods approach. This study was carried out with 74 teachers from the Faculty of Education. In the first phase of the study, pre-service teachers' prior knowledge about learning objects was defined. During the second phase of the study, a two-hour seminar was given to pre-service teachers to introduce the learning objects and the object repositories. Then, they were requested to prepare a course content and instructional plan using the object repositories. During the last phase of the study, their opinions about the object approach were determined. According to findings; before the seminar, it was observed that pre-services teachers didn't know learning objects and object repositories. Also, they didn't use learning object repositories as a reference for their courses. Pre-service teachers' preferences about learning object repositories were change according to some different factors: especially language, interaction level and resource type. Furthermore, it was seen that most of them exhibited positive attitude toward learning objects. As a conclusion, it would be worthwhile to increase the number of object repositories allowing preparation of course contents by combining objects to form a whole, in order to promote and spread use of learning object approach among teachers and preservice teachers through in-service training and pre-service training programs. Also, considering the factors affecting selection of learning objects, it would be an important step to provide support to creation of object repositories particularly in the native language, with high explanatory quality and exercise opportunities, for development and spread of use of learning objects and repositories.
Keywords: Web-based Learning; Learning Objects; Learning Object Repositories; Content Development; Education & Educational Research